Siirt İli Su Kenesi (Acari: Hydrachnidia) Faunası ve Türkiye İçin Yeni Bir Kayıt - Esen, Yunus; Erman, Orhan (Fırat University, 2015)
Bu çalışmada Siirt ilinden 2012-2013 yılları arasında toplanan su keneleri değerlendirilmiş ve toplam 13 familyaya ait 65 tür tespit edilmiştir. Tespit edilen türlerin tümü Siirt ili için yeni kayıttır. Türkiye faunası için yeni kayıt olan Monatractides (s.str.) kermanshahus Peši?, Arman, Vafaei & Saboori, 2008’un morfolojik özellikleri örneklerimiz üzerinden gözden geçirilmiş ve dünyadaki dağılışı verilmiştir.

In this study, the water mites collected from Siirt Province between 2012-2013 years were evaluated. Totally, 65 species were determined belonging to 13 families. All determined species are new records for Siirt Province. Monatractides (s.str.) kermanshahus Peši?, Arman, Vafaei & Saboori, 2008, a new record for the Turkish fauna, is reviewed the morphological features and distribution in the World.
Water Mite (Acari: Hydrachnidia) Fauna of Siirt Province and a New Record for Turkey